Are Immigrants More Left-Leaning than Natives? - Simone Moriconi; Giovanni Peri; Riccardo Turati (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze whether second generation immigrants have different political preferences relative to observationally identical host country's citizens. Using data on individual voting behavior in 22 European countries between 2001 and 2017 we characterize each vote on a left-right scale using ideological and policy position of the party from the Manifesto Project Database. In the first part of the paper we characterize the size of the "left-bias" in the vote of second generation immigrants, after controlling for a large set of individual characteristics and origin and destination country unobservable factors. We find a significant left-bias of second generation migrants relative to observationally identical natives, similar in magnitude to the association between left-bias and secondary education, or living in urban areas. We then show that this left-bias associates with stronger preferences for government intervention to reduce economic inequality, and for internationalism and multiculturalism.
Keywords: D72; J61; P16; Z10; 330; immigration; elections; Europe